Pelatihan dan Pendampingan Penggunaan Digital Marketing kepada Pelaku UMKM di Desa Saentis Kabupaten Deli Serdang - Makromatul Afifah Nasution; Ahmad Afandi (peduli riset dan pengabdian masyarakat, 2022)
SMEs in Indonesia have become an important part of the economic system in Indonesia. This is because SMEs are business units that are more numerous than large-scale industrial businesses and have the advantage of absorbing more labor and also being able to accelerate the process of equity as part of development. One of the SMEs located in Saentis Village, Deli Serdang Regency, is fried food, cosmetics and glassware. Each of these businesses has a characteristic that distinguishes it from other businesses. But these businesses still have limitations that become problems, such as their marketing strategies that are still not well organized. In this case, digital marketing is the right solution that must be done by MSME business actors. Digital marketing is the right solution because it can reach consumers more broadly and quickly